Carbazole–acenaphthene (donor–acceptor)-based luminophores for picric acid detection: a combined experimental and theoretical study. Issue 15 (14th July 2021) - Kajjam, Aravind Babu; Singh, Kasturi; Tej, R. V. Varun; Vaidyanathan, Sivakumar
Abstract : In the present investigation, carbazole–acenaphthene-based donor–acceptor luminophores were designed and synthesized. All the luminophores were used for picric acid detection. Abstract : In the present investigation, carbazole–acenaphthene-based donor–acceptor luminophores were designed and synthesized. All the luminophores showed fluorescence quenching behavior towards nitroaromatics through complex formation. All the luminophores were used for the detection of picric acid (PA) based on fluorescence quenching. All the luminophores showed the highest quenching efficiency with PA, compared with that of other explosives like 2, 4-dinitrophenol (2, 4-DNP), 4-nitrophenol (NP), benzoic acid (BA), and phenol (PH). Fluorescence quenching behavior was confirmed by 1 H NMR, fluorescence and DFT studies. The time-resolved fluorescence results indicate that the dynamic quenching mechanism is involved in PA detection. The photo-induced electron transfer (PET) from luminophores to PA was confirmed by NMR and DFT analyses. DFT calculations of luminophores with PA were also carried out to know the energy levels of the complex formed after the addition of PA. In addition, the detection limit, i.e., the photographic detection of PA, has been successfully demonstrated in the solution and solid states (TLC plates). The singlet and triplet energy states of the excited molecules were calculated through time-dependent density functional theory (TD-DFT) calculations.